Factors impacting high-level mobility in traumatic brain injury: a scoping review - Azmi, Syazlin; Nordin, Nor Azlin Mohd; Alghwiri, Alia; Manaf, Haidzir (International Journal of Public Health Science (IJPHS), 2025)
High-level mobility is crucial for improving quality of life and ensuring active participation in daily routines and community engagement. Therefore, this scoping review explored the available evidence on factors impacting high-level mobility among traumatic brain injury (TBI) individuals and the outcome measures used to evaluate high-level mobility. Following the preferred reporting items for Systematic Reviews and Meta-analyses Extension for Scoping Reviews (PRISMA-ScR) guidelines, five databases were searched: Scopus, Web of Science, Cochrane Library, Science Direct, and PubMed, yielding 109 articles, with eight meeting eligibility criteria. The keywords used in the search strategies were: traumatic brain injury, TBI, brain trauma, traumatic encephalopathy, and high-level mobility. This review revealed that the High-Level Mobility Assessment Tool (HiMAT) was identified as the most commonly used outcome measure for assessing high-level mobility. The key factors that may influence the outcome of high level mobility in people with TBI are age, sex, mechanism of injury, duration of post-traumatic amnesia, and individual endurance. The associations between individuals’ factors and outcomes in TBI studies exhibit significant variation. This can be attributed to several factors, including the diverse characteristics of TBI samples, different neurological recovery rates, methodological differences, timing of assessments, interactions between factors, and potential moderators.